`I code as much as I can because you never know what they might ask for`. The role of the coach in Performance Analysis: The view of the analyst - Mulvenna, C.; Bloyce, D.; Twist, C.; Thomson, E. (International Journal of Sports Science & Coaching, 2024)
Performance Analysis (PA) is viewed as an integral feature of soccer; however, the processes underpinning such practice are often described as simple, linear procedures. This fails to acknowledge the dynamism of PA and given increased investment and employment of analysts in professional soccer, scrutiny of the current processes and duties associated with the role would seem timely. To this purpose, eight full-time analysts in the English Football League (EFL) and English National League (National League) participated in in-depth semi-structured interviews and transcripts were subjected to inductive reflective thematic analysis. The data analysis revealed two higher-order categories (Flying solo / Coach control) and four themes classified as lower-order (PA pragmatism / Identifying indicators / The reticent coach / Autocratic presentations). The findings of this study highlight that the responsibilities of the performance analyst range from acting on their own initiative to responding to requests and instructions from the coach. Subsequently, the responsibility for individual actions/activities related to PA is dependent on what aspects of analysis are to be used, who is the recipient of the data/video/presentation, when in the relationship between analyst and coach the activities are developed and when in the match-play process they are carried out.